Penguatan implementasi Manajemen Berbasis Sekolah (MBS) di Kecamatan Tanete Rilau Kabupaten Barru - Kamaruddin Hasan; Lukman Lukman; Abd. Hakim (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This activity was carried out to develop astrengthening model of elementary school through theimplementation of School Based Management (SBM) throughthe availability of relevant school planning documents andimprovement community participation (PSM). The results ofproblems identification and potential for the implementation ofSBM at SDN 01 Pekkae in Tanete Rilau district of Barruregency shows that some activities needed beforeimplementing the program, such as 1) preparation of schoolstrategic plans based on its excellence and character education,2) preparation of excellence-based school programs, and 3)formulation of school programs based on character education.As a result of the implementation of this activity are 1) theavailability of the school strategic plan for the 2018-2023period, 2) the availability of school programs based on itsexcellence programs for the 2018/2019 academic year, and 3)the availability of school programs based on charactereducation for the 2018/2019 academic year. Through thisactivity, generally other results have also achieved: 1)Increased understanding of principals, teachers, schoolcommittees, and community leaders about school-basedmanagement; 2) Increased capacity of principals, teachers,school committee members, in implementing theimplementation of SBM in schools and in the community; and3) Increasing participation of the community in improvingschool quality.